Effect of coconut fiber and egg albumen in mortar for greener environment - Ngo, Siew Kee (2010)
This study was to investigate the effect of coconut fiber and egg albumen on mortar compressive and flexural strength. The purpose of adding coconut fiber into the mortar was due to coconut fibers had a good performance in controlling cracking in mortar whereas egg albumen act as a foam which rich in protein to strengthen the mortar. In this study, total 108 samples were prepared which were 54 cubes (150mm x 150mm x 150mm) and 54 prisms (100mm x 100mm x 500mm). 3 type of samples were tested to compare the strength development of each others that was mortar control, mortar containing 0.1% coconut fiber + 1% egg albumen ( mix A) and mortar containing 0.5% coconut fiber + 5% egg albumen (mix B). The data show that the strength of mortar added with coconut fiber and egg albumen had improved. The strength of mortar added with additive shows higher strength in water curing conditions compared to the .air curing conditions. The strength of mortar containing 0.1% coconut fiber + 1% egg albumen was higher than the mortar control whereas the mortar containing 0.5% coconut fiber ± 5% egg albumen was lower strength than the mortar control. Therefore, the mortar containing 0.1% coconut fiber and 1% egg albumen was more suitable.added in the mortar and had a better performance in water curing and the mortar containing 0.5% coconut fiber + 5% egg albumen does not encourage to be used as an additive in mortar due to its strength was lower than the mortar control.